2014
DOI: 10.1089/neu.2013.2916
|View full text |Cite
|
Sign up to set email alerts
|

Hypopituitarism in Pediatric Survivors of Inflicted Traumatic Brain Injury

Abstract: Endocrine dysfunction is common after accidental traumatic brain injury (TBI). Prevalence of endocrine dysfunction after inflicted traumatic brain injury (iTBI) is not known. The aim of this study was to examine endocrinopathy in children after moderate-to-severe iTBI. Children with previous iTBI (n = 14) were evaluated for growth/endocrine dysfunction, including anthropometric measurements and hormonal evaluation (nocturnal growth hormone [GH], thyrotropin surge, morning and low-dose adrenocorticotropin stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…As Auble et al 30 noted, this is significantly higher than the estimated prevalence of 2.5% in the general population. The differences between paediatric and adult prevalence may be explained, in addition to the methodological differences in study design, by the mechanism of TBI as we detail above.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…As Auble et al 30 noted, this is significantly higher than the estimated prevalence of 2.5% in the general population. The differences between paediatric and adult prevalence may be explained, in addition to the methodological differences in study design, by the mechanism of TBI as we detail above.…”
Section: Discussionmentioning
confidence: 69%
“…The prevalence of abnormal GH tests in the literature is variable, ranging from 4% to 15% in those studies in which patients were assessed based on clinical criteria,20 22 23 to 21–31% when provocative testing was performed regardless of the clinical status 21 25–28 30. There are some additional differences between studies, for example, their prospective or retrospective design, and the use of different tests and different cut-off criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no definite recommendation that routine endocrine evaluation should be carried out following TBI 13, 14. Auble et al .…”
Section: Discussionmentioning
confidence: 99%
“…TBI has been linked to neuroendocrine insufficiencies mediated by pituitary, such as: thyroid and adrenal functioning (Tsargarakis, Tzanela, & Dimopoulou, 2005), diabetes insipidus (Griffin, Hartley & Crow, 1976), growth hormone deficiencies (Lorenzo et al, 2006;Lopez et al, 1992), and hyperprolactinemia (Bondanelli et al, 2004). The percentage of individuals affected is high; 35-40% of individuals who sustained a TBI are estimated to have some degree of hypopituitarism, with incidence estimates of over 80% of children and adults with severe brain injuries (Auble et al, 2013;Hannon et al, 2013;Popovic, Aimaretti, Casanueva, & Ghigo, 2005;Rose & Auble, 2012). While there is at least one multi-center study that found no association between TBI and endocrine abnormalities, these findings appear to be the outlier (Kokshoorn et al, 2011).…”
Section: Incidence and Prevalence Of Endocrine Disruptionmentioning
confidence: 99%